Looking for justice: could RHM help to find it? - Aguirre-de-Mena, Juan Martín (My University, 2015)
1. What is Justice? 2. Reflections on some human perspectives of Justice 3. Approach to the concept of Social Justice 4. Social Justice and Labour Law: From a protective purpose to an inclusive one
Keywords: Recursos humanos; Justicia; Dirección de personal